Beyond impairment of virion infectivity: new activities of the Anti-HIV host cell factor SERINC5 - Sid Ahmed, Samy; Bajak, Kathrin; Fackler, Oliver Till (Viruses, 2024)
Members of the serine incorporator (SERINC) protein family exert broad antiviral activity, and many viruses encode SERINC antagonists to circumvent these restrictions. Significant new insight was recently gained into the mechanisms that mediate restriction and antagonism. In this review, we summarize our current understanding of the mode of action and relevance of SERINC proteins in HIV-1 infection. Particular focus will be placed on recent findings that provided important new mechanistic insights into the restriction of HIV-1 virion infectivity, including the discovery of SERINC’s lipid scramblase activity and its antagonism by the HIV-1 pathogenesis factor Nef. We also discuss the identification and implications of several additional antiviral activities by which SERINC proteins enhance pro-inflammatory signaling and reduce viral gene expression in myeloid cells. SERINC proteins emerge as versatile and multifunctional regulators of cell-intrinsic immunity against HIV-1 infection.
Gesehen am 18.02.2025
Titel des special issue: "Research on herpes virus fusion and entry"